Primary tumour resection may improve survival in functional well-differentiated neuroendocrine tumours metastatic to the liver. Issue 2 (February 2017) - Citterio, D.; Pusceddu, S.; Facciorusso, A.; Coppa, J.; Milione, M.; Buzzoni, R.; Bongini, M.; deBraud, F.; Mazzaferro, V.
Abstract: Background: Functional well-differentiated neuroendocrine tumours (NET) with liver metastases represent a therapeutic challenge with few alternative options in guidelines. In these patients, the role of surgical resection of the primary tumour is controversial. Patients and methods: From a regional registry collecting somatostatin analogue (SSA)-treated tumours from 1979 to 2005, a series of 139 patients presenting with symptomatic, liver-metastatic, well-differentiated NET (G1–G2, mitoses: ≤20, Ki-67: ≤20%) was prospectively collected and retrospectively analysed. Surgery on either the primary tumour or liver metastases was chosen: 1) when low perioperative risk was predictable; 2) in presence of an impending risk of obstruction, bleeding, or perforation; or 3) if liver metastases were suitable of curative or subtotal (>90%) tumour removal. Impact of the most relevant clinico-pathological parameters on survival was studied. Results: Median follow-up was 127 months and median survival was 94 months, with 138 vs. 37 months in resected vs. non-resected primary NET (p < 0.001), respectively. In the univariate analysis, prolonged survival was significantly associated with primary tumour resection (p < 0.001), resection of liver metastases (p = 0.002), site of primary (carcinoid vs. pancreatic, p = 0.018), basal chromogranin-A (CgA) <200 ng/mL (p = 0.001), and absence of diarrhea (p = 0.012). Multivariate analysis showed that primary tumour resection was an independent positive prognostic factor (HR = 3.17; 95% CI: 1.77–5.69, p < 0.001), whereas diarrhea, basal CgA ≥200 ng/mL, and high tumour load were independent negative prognostic factors. Also, in 103 patients with non-resectable liver metastases, primary tumour resection was significantly associated with prolonged survival (median 137 vs. 32 months, p < 0.0001). Conclusions: Primary tumour resection may improve survival in functional well-differentiated NET with liver metastases.